COMPARATIVE ANALYSIS REGARDING THE STUDY OF THE FINANCIAL BALANCE OF COMPANIES LISTED ON THE STOCK MARKET - Mihaela-Cristina Onica; Jalba Silvia; Nedelcu Andreea - Izabela (Risk in Contemporary Economy, 2015)
The research is based on the evaluation of the financial balance, for a sample of 3 entreprises listed in the same area of activity, taking into account financial and functional optics, in the period 2012-2013. The aim of this study is to reflect the influence of the financial balance on companies listed on the stock market and the evaluation of investment attraction. Maintaining financial balance is the main purpose of an enterprise and a necessary condition for survive.